2000
DOI: 10.1038/sj.bmt.1702516
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and economic comparison of allogeneic peripheral blood progenitor cell and bone marrow transplantation for acute lymphoblastic leukemia in children

Abstract: Summary:There is limited experience in the use of peripheral blood progenitor cells (PBPC) for allogeneic transplantation in children. In the present study we compared engraftment kinetics, incidence of acute and chronic graft-versus-host disease (GVHD) and the outcome and economic costs of allogeneic PBPCT vs BMT in children with ALL in a single institution. All children were transplanted in complete remission (CR) with a similar conditioning regimen and the same GVHD prophylaxis. Patients undergoing PBPCT ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
20
0

Year Published

2001
2001
2010
2010

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 24 publications
2
20
0
Order By: Relevance
“…In a previous publication we found a similar incidence and severity of chronic GVHD in a group of patients receiving PBSCT and a historical group given a BMT, 57 as also reported by Li et al 18 The higher rate of chronic GVHD which has been found in some studies associated with this procedure is of concern, but despite differences in the incidence of GVHD, reported EFS and OS after PBSCT are similar in all the previous studies. 18,20,21,57 PBSCT can provide important advantages for the recipient, especially in the early post-transplant period, accelerating bone marrow recovery and decreasing toxic effects of the transplant. Also, G-CSF mobilization and collection can be easily performed and well tolerated in healthy children without major complications, yielding enough numbers of progenitor cells and avoiding the risks and discomfort associated with bone marrow harvesting.…”
Section: Discussionsupporting
confidence: 66%
See 2 more Smart Citations
“…In a previous publication we found a similar incidence and severity of chronic GVHD in a group of patients receiving PBSCT and a historical group given a BMT, 57 as also reported by Li et al 18 The higher rate of chronic GVHD which has been found in some studies associated with this procedure is of concern, but despite differences in the incidence of GVHD, reported EFS and OS after PBSCT are similar in all the previous studies. 18,20,21,57 PBSCT can provide important advantages for the recipient, especially in the early post-transplant period, accelerating bone marrow recovery and decreasing toxic effects of the transplant. Also, G-CSF mobilization and collection can be easily performed and well tolerated in healthy children without major complications, yielding enough numbers of progenitor cells and avoiding the risks and discomfort associated with bone marrow harvesting.…”
Section: Discussionsupporting
confidence: 66%
“…18,20,21 Similarly, in a study performed recently at our institution, the outcome of a group of pediatric patients which underwent allogeneic BMT for the treatment of ALL and a similar group of patients which received allogeneic PBSCT was compared and significantly faster engraftment was found in the PBSCT group. 57 An inverse correlation between the CD34 + cell dose given, the post-transplant administration of MTX and the kinetics of engraftment has been noted by others. 10 In our series such a correlation was not statistically proven, probably due to the small size of our patient population.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Because of this, longer follow-up is necessary to address this controversial issue. However, despite differences in cGVHD incidences there is no reported negative influence on event-free survival in pediatric series, 15,34,35,37 which implies a similar TRM and a similar relapse incidence. One could expect a lower probability of leukemia relapse in PBPCT patients because of a cGVHD-related graft-versus-leukemia effect.…”
Section: Discussionmentioning
confidence: 98%
“…27 The relative merits of allogeneic PBSC or BM transplantation also encompass economic, psychosocial, and ethical concerns that were not investigated in the present study. Economic analyses have shown the overall costs associated with the two procedures, from the start of donor mobilization or bone marrow harvest to 100 days post transplantation, to be approximately equivalent in Canada 28 and for PBSC transplantation to be cheaper than BM transplantation by approximately 20% in the US 29 and approximately 30% in Spain 30 . In a recent US National Marrow Donor Program survey, 31 donors with experience of both procedures reported that they had found BM donation physically more difficult and more time consuming, and expressed a preference for PBSC donation.…”
Section: Yields Of Cd34mentioning
confidence: 99%